Investigating metallic cores using experiments on the physical properties of liquid iron alloys - Pommier, Anne; Driscoll, Peter E.; Fei, Yingwei; Walter, Michael J. (Frontiers in Earth Science, 2022)
An outstanding goal in planetary science is to understand how terrestrial cores evolved to have the compositions, thermal properties, and magnetic fields observed today. To achieve that aim requires the integration of datasets from space missions with laboratory experiments conducted at high pressures and temperatures. Over the past decade, technological advances have enhanced the capability to conduct in situ measurements of physical properties on samples that are analogs to planetary cores. These challenging experiments utilize large-volume presses that optimize control of pressure and temperature, and diamond-anvil cells to reach the highest pressures. In particular, the current experimental datasets of density, compressional velocity, viscosity, and thermal conductivity of iron alloys are most relevant to the core conditions of small terrestrial planets and moons. Here we review the physical properties of iron alloys measured in the laboratory at conditions relevant to the cores of Mars, the Moon, and Mercury. We discuss how these properties inform models of core composition, as well as thermal and magnetic evolution of their cores. Experimental geochemistry (in particular, metal-silicate partitioning experiments) provides additional insights into the nature and abundance of light elements within cores, as well as crystallization processes. Emphasis is placed on the Martian core to discuss the effect of chemistry on core evolution.